Factors associated with knowledge on self-administration of eye drop instillation among Glaucoma patients attending Eye clinic, Teaching Hospital Jaffna - Ameliya Rachel, J. A.; Meera, S.; Jegapragash, V.; Malaravan, M. (University of Jaffna, 2023)
Introduction: At least 2.2 billion individuals suffer from glaucoma, which is an asymptomatic chronic eye illness leading to complete blindness. Increased intraocular pressure is a clinical contributor to glaucoma; thus, to reduce intraocular pressure, ocular hypotensive eye drops are most commonly used. Unlike oral medications, patients’ knowledge on self-administration can lead to a great prognosis. As a result, good awareness, and support from healthcare professionals about eye drop instillation is crucial to lead a quality life in glaucoma patients. Objective: To assess the knowledge of self-administration of eye drop instillation and the associated factors among glaucoma patients attending Eye clinic, Teaching Hospital Jaffna. Methodology: A hospital-based descriptive cross-sectional study was carried out in 2023. A systematic random sampling method was used to identify 161 participants and an interviewer-administered questionnaire was used to collect the data. The chi-square test was performed in SPSS to find the association with knowledge and possible factors. Ethical approval was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna. Results: The total sample size was 161. The respondent rate was 87.5%. The age of the participants varied from 26 years to 83 years old with a mean age of 58.93 (SD=15.40). More than half of the participants (54%) were female and the majority of them were married (76.4%). A small portion of participants (33.6%) have educational qualifications above ordinary level. Nearly half of the participants (48.4%) had poor knowledge about self-eye drop instillation and only 11.8% of the participants had good knowledge. Although 64.6% of the patients were unable to identify the name of the drug, they were using them. The factors associated with knowledge were age (p<0.001), educational qualification (p<0.001), employment status (p<0.001), previous health education (p<0.05) and duration of disease (p<0.05). Conclusion: Knowledge on self-administration of eye instillation is poor among glaucoma patients who attend the Eye Clinic, Teaching Hospital Jaffna. It is recommended that healthcare providers should be more attentive towards patients’ knowledge regarding eye drop administration. Interventions such as demonstration programs, proper health education and distributing handouts can be carried out in future.
Keywords: Glaucoma; Knowledge; Eye drop instillation